Considering best practice standards for routine whole-genome sequencing for TB care and control - J.T. Denholm; G. de Vries; R. Anthony; E. Robinson; M. Backx; I.F. Laurenson; A.L. Seagar; H. Modestil; L. Trieu; J.S. Meissner; D.H.L. Ng; J.Y. Tay; et al. (IJTLD Open)
TB is a priority pathogen for the application of whole-genome sequencing (WGS) into routine public health practice. In low-incidence settings, a growing number of services have begun to incorporate routine WGS into standard practice. The increasing availability of real-time genomic information supports a variety of aspects of the public health response, including the detection of drug resistance, monitoring of laboratory and clinical practices, contact tracing investigations and active case finding. Optimal structures and approaches are needed to support the rapid translation of genomic information into practice and to evaluate outcomes and impact. In this consensus paper, we outline the elements needed to systemically incorporate routine WGS into the TB public health response, including the sustainability of services, multidisciplinary team models and monitoring and evaluation frameworks. If integrated in an efficient and thoughtful manner, routine WGS has the potential to significantly improve clinical TB care for individuals and the overall public health response.